Anaerobic degradation of microcystin-LR by an indigenous bacterial Enterobacter sp. YF3. Issue 21 (2nd November 2019) - Huang, Feiyu; Feng, Hai; Li, Xiaoyu; Yi, Xiping; Guo, Jian; Clara, Tezi; Yang, Fei
ABSTRACT: Microcystin-LR (MC-LR), a known hepatotoxin present in drinking water, and contaminated food and algal dietary supplements poses a threat to environmental and public health and thus needs to be removed. Previously microbial aerobic degradation was considered the predominant catabolic process for MC-LR inactivation, but the potential role of anaerobic microbes still needs to be determined. In our study an anaerobic MC-degrading bacterium Enterobacter sp. YF3 was isolated and identified that was capable of degrading MC-LR. Under optimal conditions the anaerobic Enterobacter sp. YF3 displayed a MC-degrading rate of 0.34 µg/ml/day. This process was dependent on temperature, pH and MC-LR concentration. Further the extracellular secretion of metabolites of anaerobic bacterium degraded MC-LR at 0.22 µg/ml/day. The parent MC-LR as well as two MC-degrading products was identified by high performance liquid chromatography (HPLC). The anaerobic MC-degrading Enterobacter sp. bacterium metabolized MC-LR independent of MC-degrading genes mlrABCD . Data indicate that anaerobic Enterobacter sp. YF3 produces MC-degrading products via a pathway that acts independently of mlrABCD genes which may add to the arsenal of bacteria to degrade microcystins.